Campagno, Marcelo (ed.) Pierre Clastres and the ancient societies. Buenos Aires: Program of Studies on Forms of Society and State Configurations in Antiquity-University of Buenos Aires/Miño and Dávila Editores, 2014. - Zapata, Horacio Miguel Hernán (2016)
A tight summary of the main themes and arguments is made in the articles compiled by Campagno that argue in favor of the revaluation of the work of the anthropologist Pierre Clastres and his contribution to the theoretical renewal among historians of the origins of the State